The Impact of Communication Network on Grid Management - Cezara-Liliana RAT; Octavian PROSTEAN (Communications of International Proceedings, 2021)
There is not much information available on how to design a communication network according to the specific needs of a power system. Communication networks are a quintessential requirement of any power system. The aim of this paper is to function as a guideline to the requirements of a power system as well as a means of improving communication networks used in such systems. Communication technology depends on the management level of the grid. These levels are: SG (Smart Grid), EMS (Energy Management System) and SCADA (Supervisory Control And Data Acquisition). In this paper only the main functions of EMS and SG are analyzed because the communication networks used in these systems are poorly documented as opposed to SCADA systems where there is an abundance of information available regarding communication
Keywords: SCADA; SG; EMS; communication.